A mechanistic understanding of the relationship between skin innervation and chemotherapy-induced neuropathic pain - Meregalli, Cristina; Monza, Laura; Jongen, Joost L. M. (Frontiers in Pain Research, 2022)
Neuropathic pain is a frequent complication of chemotherapy-induced peripheral neurotoxicity (CIPN). Chemotherapy-induced peripheral neuropathies may serve as a model to study mechanisms of neuropathic pain, since several other common causes of peripheral neuropathy like painful diabetic neuropathy may be due to both neuropathic and non-neuropathic pain mechanisms like ischemia and inflammation. Experimental studies are ideally suited to study changes in morphology, phenotype and electrophysiologic characteristics of primary afferent neurons that are affected by chemotherapy and to correlate these changes to behaviors reflective of evoked pain, mainly hyperalgesia and allodynia. However, hyperalgesia and allodynia may only represent one aspect of human pain, i.e., the sensory-discriminative component, while patients with CIPN often describe their pain using words like annoying, tiring and dreadful, which are affective-emotional descriptors that cannot be tested in experimental animals. To understand why some patients with CIPN develop neuropathic pain and others not, and which are the components of neuropathic pain that they are experiencing, experimental and clinical pain research should be combined. Emerging evidence suggests that changes in subsets of primary afferent nerve fibers may contribute to specific aspects of neuropathic pain in both preclinical models and in patients with CIPN. In addition, the role of cutaneous neuroimmune interactions is considered. Since obtaining dorsal root ganglia and peripheral nerves in patients is problematic, analyses performed on skin biopsies from preclinical models as well as patients provide an opportunity to study changes in primary afferent nerve fibers and to associate these changes to human pain. In addition, other biomarkers of small fiber damage in CIPN, like corneal confocal microscope and quantitative sensory testing, may be considered.